RESPON PUPUK KOMPOS DAN SUPER NASA TERHADAP PERTUMBUHAN DAN PRODUKSI KEDELAI (Glycine max (L) Merril) - selvia sutriana (UIR Press, 2015)
The aims of research to find out the main interactions and response of compost and fertilizer super nasa on the growth and production of soybean. Research conducted at the Faculty of Agriculture Experimental Farm Riau Islamic University during 4 months, i.e. from November 2014 to February 2015. The study used factorial completely randomized design, consisting of two factors, the first is a factor K (compost) comprises: 0, 25, 50 and 75 g/plant, and the second is a factor S (super nasa) comprises: 0, 5, 10 and 15 g/plant. Parameters measured were plant height, flowering age, harvesting age, number of pods per plant, weight of 100 dry seeds and contains a full percentage pods per plant. The results showed that the interaction of compost and fertilizer super nasa influenced the plant height, days to flowering, number of pods per plant and percentage pod contains a full per plant, and the best treatment was K1S2 (compost 25 g/plant and super nasa 10 g/plant). In the main compost gave an effect on all parameters wit the best treatment of 25 g/plant. In the main fertilizer super nasa had an effect on the plant height, flowering age, harvesting age, number of pods per plant and percentage of filled pods per plant contains with the best treatment of 10 g/plant.